Prevalence of 𝘈𝘗𝘖𝘓1 risk variants in HIV-positive compared to HIV-negative individuals with evidence of kidney disease - Notani, Madingaka Dorah (University of the Free State, 2023)
𝗕𝗮𝗰𝗸𝗴𝗿𝗼𝘂𝗻𝗱: Various types of kidney diseases, including HIV-associated nephropathy (HIVAN), focal segmental glomerulosclerosis (FSGS), chronic kidney disease (CKD), and end-stage renal disease (ESRD), have been associated to variants in the Apolipoprotein1 (𝘈𝘗𝘖𝘓1) gene. 𝘈𝘗𝘖𝘓1 high risk (G1 and G2) variants are exclusively found in individuals of African ancestry, because of this, 𝘈𝘗𝘖𝘓1 has been associated with kidney disease only in those with recent African ancestry. However, there is little data on the prevalence and implications of the 𝘈𝘗𝘖𝘓1 variation in HIV-positive patients in the South African population. 𝗔𝗶𝗺: The aim was to determine whether the 𝘈𝘗𝘖𝘓1 gene variants are present and whether genetic susceptibility along with HIV infection contributes to the development of kidney diseases, in a South African population, treated in Bloemfontein. 𝗠𝗲𝘁𝗵𝗼𝗱𝘀: This was a case-control study that included two hundred and twenty (n=220) participants consisting of four groups, namely: HIV positive with kidney disease indicators (n=55); HIV positive without kidney disease (n=55); HIV negative with kidney disease indicators (n=55) and HIV negative without kidney disease (n=55). The participant samples were selected from archived material according to the inclusion and exclusion criteria. Genotyping analysis using qPCR was performed to detect the 𝘈𝘗𝘖𝘓1 G1 and G2 variants. Sanger sequencing was used for confirmation. 𝗥𝗲𝘀𝘂𝗹𝘁𝘀 𝗮𝗻𝗱 𝗗𝗶𝘀𝗰𝘂𝘀𝘀𝗶𝗼𝗻: The frequencies of the 𝘈𝘗𝘖𝘓1 high risk genotypes revealed that the G2 variant was more prevalent than G1 in the entire study population. The frequencies were 0.0045 for 𝘈𝘗𝘖𝘓1 G1/G1, the 1000 Genome Africa found the frequency of 0.080. For G1/G2 (compound heterozygote) the frequency was 0.014. The frequency was higher for G2/G2 for this study (0.0455) compared to the 1000 genome Africa at 0.017. The prevalence of 𝘈𝘗𝘖𝘓1 G2 was higher than G1; this does not collaborate with 1000 Genome project. The p-value for 𝘈𝘗𝘖𝘓1 G2 was 0.752. There are no statistically significant associations found between the genotypes categorized by risk and either HIV or CKD. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻: The study identified the presence of all the tested 𝘈𝘗𝘖𝘓1 risk variants linked to chronic kidney disease (CKD) within a specific demographic (individuals of African descent in the South African population). The prevalence of the 𝘈𝘗𝘖𝘓1 G2 variant was more than that of the 𝘈𝘗𝘖𝘓1 G1 variant. This study did not discover any statistical significance linking 𝘈𝘗𝘖𝘓1 high-risk genotypes with the occurrence of chronic kidney disease in either HIV-positive or negative individuals. Despite this, the established connection between these factors highlights the importance of screening patients who are of African ancestry, HIV-positive, and have CKD for potential personalized treatment options. Further studies with larger samples sizes and kidney biopsies are recommended to confirm whether variants of 𝘈𝘗𝘖𝘓1 contribute to the development of kidney disease in HIV positive individuals.
Dissertation (M.Sc.(Genetics))--University of the Free State, 2023
Keywords: CKD (Chronic Kidney Disease); HIV; 𝘈𝘗𝘖𝘓1; Genotype; Risk variants; African ancestry; Human African trypanosomiasis; HIVAN; Genotype; Kidney disease markers; Chronic kidney failure; Apolipoproteins; Human genetics - Variation; Kidneys - Diseases